POTENSI PENGEMBANGAN DESA WISATA TERINTEGRASI YANG BERKELANJUTAN: STUDI KASUS DESA KEBOCORAN, KECAMATAN KEDUNGBANTENG, KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2023)
The development of the tourism sector in rural areas is increasingly integrated in the value chain with other sectors such as agriculture, industry, and healthy and natural lifestyles in the digital era. This study aims to explore the potentials and obstacles in developing sustainable tourism development values in integrated business-based rural areas. The research was conducted using an exploratory qualitative approach through case studies. The research was conducted at the tourism potential of Leakage Village, Kedungbanteng District, Banyumas Regency. Data collection was carried out through direct observation and study of documents from various sources such as books, papers, articles published online from internet media. Potential analysis was carried out through Focus Group Discussions (FGD) with local communities and academics, namely members of the community service team for the Architecture Study Program, Wijayakusuma University, Purwokerto. The data were processed qualitatively using open coding, axial coding, and selective coding methods. The results of the study found that the potential of integrated tourism villages in rural areas such as: nature tourism, agro-tourism, history, culinary, green-health-natural tourism, and local tourism, for the development of added value in the agricultural and industrial sectors in rural areas